Social Work, Sociometry, and Psychodrama Experiential Approaches for Group Therapists, Community Leaders, and Social Workers - Giacomucci, Scott (Psychodrama in Counselling, Coaching and Education, 2021)
This open access book outlines the intersections between social work and the methods of sociometry and psychodrama. Different sections offer essential practice wisdom for both trauma-focused and trauma-informed experiential work for individuals, groups, organizations, and communities. This text enriches the understanding of various action-based approaches and highlights how to enliven social work practice. The chapters include clinical vignettes and examples of structured sociometric prompts with diverse populations, topics, and social work settings to enhance the understanding of group practice, individual practice, and community practice. It provides social workers and other professionals with dynamic tools to improve assessment, intervention, activism, and leadership. Strength-based practical tools are offered to readers, along with guidance for theoretical conceptualizations. This integrative book is an essential read for students, practitioners, leaders, and scholars within the fields of social work, psychodrama, the creative art therapies, group therapy, community organizing, and social activism.